Entrepreneurial Bricolage to Facing Resource Constraint in Small Industry of Brown Cane Sugar - Gusfa Arlian Putra; Muhammad Romli; Yandra Arkeman (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
Bricolage theory, making do what is at hand, describes entrepreneurs' activities to sustain the business in a penurious environment. It is believed could not only develop the business but also trigger innovativeness, creativity, and sustainability. This research intends to discover how entrepreneurs overcome resource constraints using bricolage. It also aims to find the relationship between bricolage and entrepreneurs' demographic and innovative personality. The study was conducted from April to June 2020 in Central Aceh Regency. Using a survey and questionnaire to collect the data towards 26 entrepreneurs of brown cane sugar reveals that human resource is a significant constraint when running the business, specifically in finding an appropriate and loyal team member. Using bricolage, they refuse to enact with limitation by hiring people from surronding even their family members to work in this business. Meanwhile, many entrepreneurs have the resource at hand in the form of capital and knowledge since they have spent a lot of time working in similar businesses before building their brown sugar. Despite weak correlation, the relationship between variables is positive except for age and education. Bricolage and innovative personality have a weak positive correlation which means that this industry is less innovative. This research also become fundamental literature for similar future research. Keywords: bricolage, resource constraint innovative personality, small industry